Review on Murraya koenigii: Dietary Supplements and Highly Prosperous Plants of Pharmacological Value - Gahtori, Kavita; Aggarwal, Chanchal; Tyagi, Manjusha; Bajpai, Atal Bihari; Srivastava, Naina; Singh, Shalini; Singh, Shelly; Gaurav, Naveen (The Scientific Temper, 2022)
Murraya koenigii (Curry tree) is a common culinary plant, its leaves are used from ancient times as a spice or merely as garnishing or seasoning and they not only enhance the flavor but also increase the nutritional value of food. Besides being a valuable ingredient curry plant has high medicinal value, it is being used since ancient times to treat various diseases, heal wounds, and also has cosmetic uses. This review highlights the morphological and taxonomical status of the curry plant along with its phytochemicals, pharmacological activity, medical importance, and ethnobotanical uses.